2020
DOI: 10.1097/gox.0000000000003266
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Pass/Fail Step 1 Scoring: Plastic Surgery Program Director and Applicant Perspective

Abstract: Background: As early as 2022, United States Medical Licensing Examination Step 1 results will be reported as pass or fail, rather than as 3-digit numeric scores. This survey examines the perspectives of plastic surgery applicants and program directors (PD) regarding this score reporting change. Methods: A 24-item survey was distributed to integrated applicants from the 2018–19 and 2019–20 application cycles. An analogous 28-item survey was sent to integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 27 publications
4
51
0
Order By: Relevance
“…The aim of this study was to compare the perceptions among program directors (PDs) in orthopaedics and IM on the change of Step 1 from a graded to a pass/fail exam, and its impact on the residency application process. Some groups have studied PD opinions of the Step 1 pass/fail change; however, to the best of our knowledge, the current study is the first comprehensive survey to directly compare the impact on medicine and a surgical subspecialty [4][5][6][7][8][9][10][11][12]. We chose to study IM PDs because IM has historically been a popular specialty that has had the most number of total applicants.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to compare the perceptions among program directors (PDs) in orthopaedics and IM on the change of Step 1 from a graded to a pass/fail exam, and its impact on the residency application process. Some groups have studied PD opinions of the Step 1 pass/fail change; however, to the best of our knowledge, the current study is the first comprehensive survey to directly compare the impact on medicine and a surgical subspecialty [4][5][6][7][8][9][10][11][12]. We chose to study IM PDs because IM has historically been a popular specialty that has had the most number of total applicants.…”
Section: Introductionmentioning
confidence: 99%
“…Cutoff scores on USMLE Step 1 have been described in the literature, ranging from scores of 190–245+. 22 , 23 However, with the transition of W to a pass/fail system, Step 2 Clinical Knowledge (CK) may become a new metric for cutoff, 24 and applicant familiarity will likely become a more important factor. 25 Further, as mentioned previously, many have reported that membership in AOA is often considered in evaluation.…”
Section: What Program Directors Look Formentioning
confidence: 99%
“…The new pass/fail method of step 1 yields room for school reputation, and thus prestige, to serve as a pertinent factor in applicant selection. 4 One may assume that if an institution has a substantial amount of grant money and has consequently established an IRP, as shown in our results, this combined sense of prestige may positively influence a student's outcome in matching to PS.…”
mentioning
confidence: 59%